Determination of the Response Spectra of the Superstructure of Length l=3X63.0 m - Nugzar Rurua; Boris Maisuradze; Ioseb Utmelidze (AGG+)
During a seismic impact, the main emphasis is placed on the damage to bridge piers, which were isolated from the horizontal earthquake detector. Accordingly, when calculating the bridges, the reaction spectra obtained from the horizontal earthquake detector are used both for the piers and for the superstructure. The issue of seismic resistance of bridges is very important, especially for superstructures with long spans. It is necessary to construct dynamic curves of seismic resistance for superstructures of a specific system. The article deals with composite steel and concrete continuous span superstructure with a scheme L=3x63.0 m, on which we performed seven real earthquake records for all three categories of soil using the direct dynamic method and built the reference response spectra. Based on the obtained response spectrum and the methodology provided by different normative documents, the calculation of the selected superstructure was carried out, and the force values were determined. Discussion: On the basis of the results obtained with the reference response spectra and the curves given in the normative documentation, graphs were drawn, and composite steel and concrete continuous span superstructure with a scheme L=3x63.0 m of the vertical response spectra was determined.